Searching for bacteria able to metabolize polycyclic aromatic sulfur compounds in 12-years periodically fed bioreactor - Matos Neto, Gilberto [UNESP]; Marques, Eric de Lima Silva; Oliveira, Larissa Karen Silva; Rezende, Rachel Passos; Dias, João Carlos Teixeira (Springer Nature, 2023)
Biodesulfurization is a promising alternative for removing sulfur molecules from the polycyclic aromatic sulfur compounds (PASC) found in petroleum. PASC consists of recalcitrant molecules that can degrade fuel quality and cause a range of health and environmental problems. Therefore, identifying bacteria capable of degrading PASC is essential for handling these recalcitrant molecules. Microorganisms in environments exposed to petroleum derivatives have evolved specific enzymatic machinery, such as the 4S pathway associated with the dszABC genes, which are directly linked to sulfur removal and utilization as nutrient sources in the biodesulfurization process. In this study, bacteria were isolated from a bioreactor containing landfarm soil that had been periodically fed with petroleum for 12 years, using a medium containing dibenzothiophene (DBT), 4.6-dimethylbenzothiophene, 4-methylbenzothiophene, or benzothiophene. This study aimed to identify microorganisms capable of degrading PASC in such environments. Among the 20 colonies isolated from an inoculum containing DBT as the sole sulfur source, only four isolates exhibited amplification of the dszA gene in the dszABC operon. The production of 2-hydroxybiphenyl (HPB) and a decrease in DBT were detected during the growth curve and resting cell assays. The isolates were identified using 16S rRNA sequencing belonging to the genera Stutzerimonas and Pseudomonas. These isolates demonstrated significant potential for biodesulfurization and/or degradation of PASC. All isolates possessed the potential to be utilized in the biotechnological processes of biodesulfurization and degradation of recalcitrant PASC molecules.
Keywords: Biodegradation; Dibenzothiophene; dsz genes; Evolutionary engineering